Pendugaan Skala Usaha Usahatani Padi Sawah dengan Fungsi Keuntungan - Handewi Purwati S. Rachman (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1987)
EnglishThis research estimates the short run rice farming returns to scale condition by using Cobb-Douglas profit function model. Size of rice field is assumed as fixed input. Data from six desas in the area of Cimanuk River Basin, West Java, collected by Rural Dynamic Study were analyzed. The analysis was based on the rainy season 1982/1983 data. Results of this analysis show the average size of rice area 0.433 ha has not given a maximum profit yet, and the rice farming activities is at the